1985
DOI: 10.1111/j.1365-2125.1985.tb05063.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enalapril on baroreceptor mediated reflex function in normotensive subjects.

Abstract: The effects of enalapril, 20 mg orally, on the responses to baroreflex activation and deactivation by respectively phenylephrine and nitroglycerin were investigated in normotensive subjects on a normal sodium diet, with simultaneous measurement of plasma renin activity (PRA), converting enzyme activity (PCEA), aldosterone and catecholamines. Enalapril, 4 h after administration, lowered artificial blood pressure without modifying heart rate and plasma catecholamines. PCEA was abolished, PRA increased and plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…The same finding was reported in normotensive man by Giudicelli et al (1985) and they also concluded that resetting of the baroreflexes accounted for the lack of reflex tachycardia during enarapril treatment. However, such baroreflex resetting would not fully explain the finding that norepinephrine abolished the production of reflex tachycardia by captopril in rabbits.…”
Section: Discussionsupporting
confidence: 80%
“…The same finding was reported in normotensive man by Giudicelli et al (1985) and they also concluded that resetting of the baroreflexes accounted for the lack of reflex tachycardia during enarapril treatment. However, such baroreflex resetting would not fully explain the finding that norepinephrine abolished the production of reflex tachycardia by captopril in rabbits.…”
Section: Discussionsupporting
confidence: 80%
“…16 One of the characteristics of ACEis is that they lower peripheral vascular resistance without causing a compensatory increase in heart rate [17][18][19][20] or changing baroreceptor activity. 21 They also show lack of reflex tachycardia 22 and cause inhibition of the normal tonic influence of Ang II on the sympathetic nervous system. 23 During ACE inhibition, heart rate responses to postural changes and exercise are not impaired.…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 99%
“…In a recent article in the Journal, Giudicelli et al (1985) reported on the influence of enalapril on baroreflexes in an attempt to explain the absence of tachycardia with blood pressure reduction, a characteristic haemodynamic feature of angiotensin converting enzyme (ACE) inhibitors. Their focus was mainly on baroreceptor reflexes, hence their article somehow obscures other possible explanations for the absence of reflex cardioacceleration including (1) a central sympatho-inhibitory action, (2) removal of the peripheral angiotensin II (All) mediated presynaptic facilitation of noradrenaline release, (3) unchanged arterial wall tangential tension during ACE inhibition, (4) selective venodilatation or (5) parasympathetic activation.…”
mentioning
confidence: 99%